Therapeutic Management of COVID-19 in a Pediatric Patient with Neurodegenerative CLN2 Disease and ICV—Enzyme Replacement Therapy: A Case Report - Schwering, Christoph; Apostolidou, Sofia; Deindl, Philipp; Christner, Martin; Knobloch, Johannes K.-M.; Herrmann, Jochen; Kobbe, Robin; Schulz, Angela; Singer, Dominique; Ebenebe, Chinedu Ulrich (Neuropediatrics, 2022)
The 12 years old male patient presented here suffers from neuronal ceroid lipofuscinoses 2 (CLN2) (MIM# 204500) and receives intracerebroventricular enzyme replacement therapy (ICV-ERT) every 14 days. After the emergence of the coronavirus disease 2019 (COVID-19) pandemic, routine care of children and adolescents with rare chronic diseases has become challenging. Although, in general, children do not develop severe COVID-19, when severe acute respiratory syndrome coronavirus 2 infection was detected by polymerase chain reaction-screening examination in our CLN2 patient before hospital admission for ICV-ERT, he was regarded to be at risk. Upon diagnosis, the patient developed respiratory deterioration symptoms and was admitted to our pediatric intensive care unit to receive oxygen, remdesivir, and steroids. As far as we know, this is the first CLN2 patient receiving intraventricular enzyme therapy with COVID-19 who required intensive care treatment and specific therapy.
Keywords: CLN2 disease; SARS-CoV-2; respiratory symptom; COVID-19